2011
DOI: 10.1136/bjophthalmol-2011-300304
|View full text |Cite
|
Sign up to set email alerts
|

Population-based incidence of exudative age-related macular degeneration and ranibizumab treatment load

Abstract: These data allow an estimation of the incidence of exudative AMD in a Caucasian population and the treatment load with ranibizumab, which may help plan anti-vascular endothelial growth factor treatment programmes and estimate costs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 19 publications
0
12
0
1
Order By: Relevance
“…The Blue Mountains Eye Study found a 10-year neovascular AMD incidence of 2.2% for patients past the age of 49 years, 2.0% for those from 60–69 years, and 12.4% for those 80 years and older [4]. Similar average incidence rates were found in a comprehensive study of the Icelandic population [5]. …”
Section: Introductionmentioning
confidence: 57%
“…The Blue Mountains Eye Study found a 10-year neovascular AMD incidence of 2.2% for patients past the age of 49 years, 2.0% for those from 60–69 years, and 12.4% for those 80 years and older [4]. Similar average incidence rates were found in a comprehensive study of the Icelandic population [5]. …”
Section: Introductionmentioning
confidence: 57%
“…Both genetic susceptibility and behavioral and lifestyle factors modify the risk of developing AMD [23]. As seen also in this study, AMD has a strong association with age [4, 6-12, 21-23]. Other risk factors associated with AMD include cigarette smoking, previous cataract surgery, higher body mass index, history of cardiovascular disease, hypertension, diabetes, and higher plasma fibrinogen [21-23].…”
Section: Discussionmentioning
confidence: 74%
“…Accordingly, in this study the 146 new patients with exudative AMD should need a mean 818 (range 438-1898) injections per year. Approximately 1200 injections were given in Iceland for the on average 147 exudative AMD patients per year which suits well with the range of the suggested regimen [4]. …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations